Richard - Myers, Benjamin, 1976- (London : Picador, 2010)
Set in the 1980s and 90s, in Cardiff, London and America,'Richard' tells the story of Richard Edwards as he might have told it. A story of hope and despair in equal measure, it's an account of an unhappy young man who'll try anything and everything to get some peace from the voice in his head that tells him he's useless, that he'd be better off dead. He drinks, takes risks and drugs both, and even cuts himself sometimes, because physical pain can be easier to bear than emotional. He can't play a musical instrument, but that doesn't stop him from joining a band - and as that band becomes more and more successful (record deals and interviews in the music press; national and international tours, and managers who seem to have bottomless pockets), it seems he might just be okay after all. But the demons that nag at him won't be easily assuaged, and ultimately, he has to decide whether or not he has a future. The story of a band looking to make it big and a young, troubled soul looking just to make it through the night,'Richard' marks the arrival of a dazzling new talent.
Keywords: Edwards, Richey, -- 1967- -- Fiction; Manic Street Preachers (Musical group) -- Fiction; Missing persons -- Fiction; Rock musicians -- Fiction